PEMETAAN DIMENSI KUALITAS PELAYANAN KESEHATAN HEWAN DARI PERSPEKTIF PENYEDIA DAN PENERIMA PELAYANAN MEDIS VETERINER - Alan Chandrasaputra; Adi Utarini; Ida Tjahajati (Journal of Health Service Management, 2021)
Background: The increasing demand for veterinary medical service quality from community has been increasing as seen on the raising of lawsuit for veterinary services since 2008. The description of veterinary healthcare service quality in Indonesia was still unclear which part of quality dimension play the role to describe quality in veterinary healthcare service, especially in clinical area. Objective: This study aimed to determine the dimensions that influence the quality of veterinary medical services from the perspective and expectations of clients and providers. Methods: Qualitative Explorative as research design. Data Collection was done by 17 In-Depth Interview with 14 service providers and 3 service clients with addition 1 panel interview with 4 cat owner from cat lovers community and 1 panel interview with 2 dog owner. All respondent must have experienced with providing/receiving veterinary healthcare service. Interview Data then transcribed followed with Coding, Categorizing, and being made into Themes with Atlas.ti application which Themes become the fundamental of Quality Dimension of Veterinary Healthcare service. Results: The interview produced 20 transcripts that were coded subcategory categories-themes. The results of the categories obtained have the capacity as a dimension of the quality of veterinary medical services in the form of: managerial services; internal provider communication; professionalism of the provider; service competency, communication skills; client education, honesty and transparency; service security; service facilities; the dynamics of the world of service; service outputs and outcomes; and client assurance. Conclusion: The category becomes the dimension of service quality in D.I. Yogyakarta contains 11 service quality dimensions which are divided into 3 themes. The theme is the value of service; communication and interaction between service providers and clients; and clients demands. This theme affects the veterinary medical services especially in the D.I area. Yogyakarta.